Nach dem 11. September: NATO putzmunter oder am Ende? - Cremer, Ulrich (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2002)
After September 11 the military factor has increased, in NATO countries additional funds are allocated to arming. Unfortunately UN lose ground, as neither US nor NATO accept the UN monopoly on the use of force any more. NATO war against Yugoslavia in 1999 - not based on UN security council mandate - was not an exception. September 11 has catalyst function for political and military development already under way since 1991 when NATO updated Strategie Concept in Rome, decided for out-of.area missions and already saw the risk of terrorist acts. New NATO means an aggressive military network of meanwhile 46 nations in Europe including Russia. The war against terrorism smoothes the way for global „North Alliance" menacing the South. In future, the cooperation NATO-Russia will intensify. Within NATO the predominance of US over Western Europe is increasing. US leadership is not challenged in the next years as the EU plans for autonomous intervention forces still lade military key capabilities. As NATO provides for interoperability between NATO members and NATO Partnership for Peace countries as well it will maintain its important function for US. Thus, they will not give up NATO.